ECTO AND ENDOPARASITES OF BATS IN SELECTED AREAS OF LAFIA METROPOLIS, NASARAWA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2025)
Bats harbor parasites, increasing disease surveillance. Between November 2022 and January 2023, a survey in Lafia metropolis employed mist nets over 12 nights across six areas to assess bats ecto and endoparasites prevalence. Two hundred and nineteen bats were trapped, belonging to five species: Tadarida brasiliensis (139), Eidolon helvum (32), Afronycteris nanus (16), Scotophilus leucogaster (16), and Rhinolophus lander (16). Ectoparasites comprising four genera: Ixodes, Thaumapsylla, Nycteribia and Demodex; and endoparasites belonging to three groups: Nematodes, Protozoans and Cestodes) showed an overall prevalence (3.65%) and (10.04%) respectively. Locations based prevalence of ecto and endoparasites  revealed  Phase II recorded the highest prevalence (37.5%), with a significant difference (X² = 0, df = 5, p < 0.001) and Mararaba had the highest prevalence (31.18%), with a very high variation (X² = 36.358, df = 5, p < 0.0001). Prevalence of Ectoparasites, and endoparasites  in relation to sex was higher in females (62.5%) than in males (37.5%) with significant  difference (X² = 6.25, df = 1, p = 0.01242)  and higher in males (63.64%) than in females (36.36%) varied significantly (X² = 7.442, df = 1, p < 0.006372). Ectoparasites of bats in relation to species revealed E. helvum recorded the highest prevalence (50%), with a significant difference (X² = 103.12, df = 4, p < 0.0001), for endoparasites, T. brasiliensis had the highest distribution (50%), with a significant difference (X² = 71.503, df = 4, p < 0.0001). Further research across the state is needed for a better understanding of bats parasites.
Keywords: Prevalence; Species; Sex; Locations